Halosbaena okinawaensis, a new species of Thermosbaenacea (Crustacea) from submarine cave on Okinawa Island, Ryukyu Islands, southwestern Japan - Sihmomura, Michitaka; Fujita, Yoshihisa (Zootaxa, 2017)
A new thermosbaenacean, Halosbaena okinawaensis sp. nov. is described from a submarine cave in Okinawa Island, Ryukyu Islands, southwestern Japan. The species differs from its congeners in having a subtrapezoidal exopod segment 1 of pereiopods 2–6, a curved penial lobe, and a telson with a pair of simple macrosetae subdistally on dorsal surface.